Emotional Distress, Attitudes and Beliefs of Youth in Pandemic Context. The Case of Constanta County - Salceanu, Claudia; Călin, Mariana Floricica (Technium Social Sciences Journal, 2022)
The COVID-19 pandemic had an unprecedented overall impact on the Romanian people. Just like the rest of the world, the Romanian people had to deal with the consequences of the dramatic changes that took place in their everyday life. A sample of 3503 young people, all residents of Constanta County, aged between 19 and 25 years old, was assessed with two questionnaires: The Emotional Distress Profile and Attitudes and Beliefs Survey. The purpose of the study is to identify significant differences between rural and urban residents, regarding these two psychological dimensions. Our results show that youth in the rural environment state their much more distressed and have much more irrational beliefs than those in urban environment. Results are discussed at the end of the paper in the context of the preparations people have to make in face of the COVID-19 fifth wave that is coming.